Non-aqueous electrolyte and lithium secondary battery comprising same
By using oxazolidinone and propargyl imidazole compounds as additives in lithium secondary batteries, a stable SEI film is formed, which solves the problems of positive electrode degradation and negative electrode SEI film passivation at high temperatures, and improves the high-temperature stability and cycle characteristics of the battery.
Patent Information
- Application Number
- CN202380043321.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2023-12-08
- Publication Date
- 2025-01-10
AI Technical Summary
Existing lithium secondary batteries are prone to positive electrode degradation, transition metal ion dissolution, and reduced passivation capability of the negative electrode SEI film at high temperatures, resulting in poor cycle characteristics and high-temperature stability, as well as severe battery swelling.
A non-aqueous electrolyte containing oxazolidinone compounds and propargyl imidazole compounds as additives is used to form a stable SEI film on the positive and negative electrode surfaces, thereby inhibiting the dissolution of transition metal ions and the degradation of the negative electrode, and improving the high-temperature stability and cycle characteristics of lithium secondary batteries.
It effectively suppresses the deterioration of the passivation ability of the SEI film at high temperatures, prevents the deterioration of the negative electrode, improves the charge-discharge characteristics and output characteristics of the lithium secondary battery, reduces the volume expansion of the battery, and improves the overall performance of the battery.
Smart Images

Figure CN119301791A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0171006, filed on December 8, 2022, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a non-aqueous electrolyte and a lithium secondary battery comprising the same. Background Art
[0004] Recently, as the application fields of lithium secondary batteries have rapidly expanded not only to power sources of electronic devices such as electricity, electronics, communications and computers, but also to power storage power sources of large devices such as automobiles and power storage devices, the demand for secondary batteries with high capacity, high output and high stability has increased.
[0005] In particular, in lithium secondary batteries for automobiles, high capacity, high output and long service life characteristics have become important. In order to increase the capacity of secondary batteries, high nickel positive electrode active materials with high energy density but low stability can be used, or secondary batteries can be driven at high voltage.
[0006] However, when the secondary battery is driven under the above conditions, as charging and discharging proceed, the surface structure of the electrode or the film formed on the positive / negative electrode surface deteriorates due to side reactions caused by electrolyte degradation, so transition metal ions may be dissolved from the positive electrode surface. As described above, since the dissolved transition metal ions are electrodeposited on the negative electrode and the passivation ability of the solid electrolyte interphase (SEI) is reduced, the problem of negative electrode degradation occurs.
[0007] This deterioration phenomenon of the secondary battery tends to be further accelerated when the potential of the positive electrode increases or when the battery is exposed to high temperature, and there occurs a problem that the cycle characteristics of the secondary battery deteriorate due to the deterioration phenomenon.
[0008] Furthermore, when a lithium-ion battery is used continuously for a long time or placed at a high temperature, gas is generated, thereby causing a so-called swelling phenomenon in which the battery thickness increases, and it is known that the amount of gas generated in this case depends on the state of SEI.
[0009] Therefore, in order to solve these problems, attempts have been made to study and develop methods capable of suppressing the dissolution of metal ions from the positive electrode and forming a stable SEI film on the negative electrode, thereby reducing the swelling phenomenon of the secondary battery and improving the high temperature stability. Summary of the invention
[0010] Technical issues
[0011] As a result of various studies conducted to address this limitation, one aspect of the present invention provides a non-aqueous electrolyte having improved high temperature stability by suppressing degradation of the positive electrode, reducing side reactions on the positive electrode and in the electrolyte, and forming a stable SEI film on the negative electrode.
[0012] That is, one aspect of the present invention also provides a lithium secondary battery having improved overall performance such as high-temperature cycle characteristics, high-temperature storage characteristics, and thermal stability by including the above-mentioned non-aqueous electrolyte.
[0013] Technical Solution
[0014] According to one aspect of the present invention, there is provided a non-aqueous electrolyte comprising: a lithium salt, an organic solvent, a compound represented by the following formula 1 as a first additive, and a compound represented by the following formula 2 or formula 3 as a second additive.
[0015] [Formula 1]
[0016]
[0017] In the above formula 1, R1 is any one selected from the group consisting of an alkyl group having 1 to 5 carbon atoms that can be substituted with fluorine, an alkenyl group having 2 to 5 carbon atoms that can be substituted with fluorine, an alkynyl group having 2 to 5 carbon atoms that can be substituted with fluorine, S02R' and COR', R' is any one selected from the group consisting of an alkyl group having 1 to 5 carbon atoms that can be substituted with fluorine, an alkenyl group having 2 to 5 carbon atoms that can be substituted with fluorine and an alkynyl group having 2 to 5 carbon atoms that can be substituted with fluorine, and R2 and R3 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 5 carbon atoms and an alkoxy group having 1 to 5 carbon atoms.
[0018] [Formula 2]
[0019]
[0020] In the above Formula 2, R is an alkylene group having 1 to 3 carbon atoms which may be substituted with fluorine, and R4 to R6 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 3 carbon atoms, and a nitrile group.
[0021] [Formula 3]
[0022]
[0023] In the above Formula 3, R7 is an alkylene group having 1 to 8 carbon atoms which may be substituted with fluorine, and R8 is any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
[0024] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery including the above-mentioned non-aqueous electrolyte.
[0025] Beneficial effects
[0026] The compound of the above formula 1 provided as the first additive of the present invention is an oxazolidinone compound, and its ring structure breaks on the positive and negative electrode surfaces to easily form a film. Specifically, since the carbon with lower electronegativity than nitrogen and oxygen in the oxazolidinone ring also has a lower electron density than nitrogen and oxygen in the oxazolidinone ring, carbon is easily reduced on the negative electrode so as to form a film. On the contrary, due to the increase in the oxidation number of the transition metal of the positive active material on the positive electrode during charging, the oxygen of C=O in the oxazolidinone ring interacts strongly with the positive electrode, the ring structure may break, and a film may be easily formed. Since the oxazolidinone ring structure breaks into a free radical form to cause an additional cross-linking reaction, a strong and stable film can be formed. In addition, since the nitrogen and oxygen in the oxazolidinone ring structure have unshared electron pairs, when the lithium ions are lithiated / de-lithiated to the positive / negative electrode, a film with high lithium mobility is formed. Therefore, the first additive of the present invention can suppress the deterioration of the passivation ability of SEI at high temperatures, thereby preventing the degradation of the negative electrode and improving the performance of the lithium secondary battery.
[0027] The compound of the above formula 2 or 3 provided as the second additive of the present invention contains a propargyl group in the molecule to help improve high temperature durability. The SEI film prepared by the reduction reaction of the compound of the above formula 2 or 3 on the negative electrode contains a propargyl group, and the propargyl group becomes a cross-linking site in the SEI to enable additional reactions. Since a strong SEI film is formed by an additional cross-linking reaction, the performance degradation caused by the electro-deposition of transition metals dissolved from the positive electrode on the negative electrode can be effectively suppressed. In addition, the cyclic carbonate functional group and the imidazole functional group contained in the additive of the above formula 2 or 3 can effectively suppress the degradation of the positive electrode and the side reaction on the positive electrode surface to improve performance and reduce the dissolution of transition metals occurring during charging. That is, the compound of the above formula 2 or 3 provided as the second additive of the non-aqueous electrolyte of the present invention can form a stable ion conductive membrane on the positive and negative electrode surfaces.
[0028] Therefore, when using the non-aqueous electrolyte of the present invention comprising the first additive and the second additive, the film-forming reaction of the second additive is accelerated by the free radicals generated when the ring structure of the first additive is broken. Due to the structure caused by oxazolidinone, imidazole, cyclic carbonate structure or the structure caused by the aliphatic alkyl film, the film formed by the interaction of the first additive and the second additive can have excellent lithium ion transfer characteristics to improve the charge and discharge characteristics and output characteristics of the lithium secondary battery. The film formed by the interaction of the first additive and the second additive can have excellent oxidation resistance, thereby suppressing the side reactions occurring on the film of the positive and negative electrodes even in the acidic atmosphere of the electrolyte. In addition, the film formed by the interaction of the first additive and the second additive has excellent durability, even resisting the volume expansion of the negative electrode occurring during charging and discharging. Therefore, the non-aqueous electrolyte of the present invention can form an electrode-electrolyte interface that is stable and durable at high temperatures, and can suppress unnecessary electrolyte decomposition side reactions, thereby realizing a lithium secondary battery with improved overall performance. DETAILED DESCRIPTION
[0029] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should also be understood that based on the inventor can appropriately define the meanings of the words or terms to best explain the principles of the present invention, the words or terms should be interpreted as having a meaning consistent with its meaning in the context of the relevant technologies and technical ideas of the present invention.
[0030] Terms such as “including” or “having” are intended to indicate the presence of features, quantities, steps, components or a combination thereof described in the specification, and it should be understood that they do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, components or a combination thereof.
[0031] In addition, "a" and "b" in the description of "a to b carbon atoms" in the present disclosure refer to the number of carbon atoms contained in a particular functional group. That is, the functional group may include "a" to "b" carbon atoms. For example, "alkylene having 1 to 5 carbon atoms" refers to an alkylene containing 1 to 5 carbon atoms, i.e., -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH3)CH-, -CH(CH3)CH2-, -CH(CH3)CH2CH2-, etc.
[0032] Furthermore, the "alkylene group" in the present disclosure means a branched or unbranched divalent saturated hydrocarbon group.
[0033] In addition, all alkyl groups in the present invention may be substituted or unsubstituted. Unless otherwise defined, "substituted" means that at least one hydrogen bonded to a carbon is replaced by an element other than hydrogen, such as an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, a heterocycloalkyl group having 3 to 12 carbon atoms, a heterocycloalkenyl group having 3 to 12 carbon atoms, an aryloxy group having 6 to 12 carbon atoms, a halogen atom, a fluoroalkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a heteroaryl group having 2 to 20 carbon atoms, a halogenated aryl group having 6 to 20 carbon atoms, a nitro group, a nitrile group, etc.
[0034] Hereinafter, the present invention will be described in more detail.
[0035] Non-aqueous electrolytes
[0036] The non-aqueous electrolyte of the present invention may include a lithium salt, an organic solvent, a compound of the following Formula 1 as a first additive, and a compound of the following Formula 2 or 3 as a second additive.
[0037] The non-aqueous electrolyte of the present invention includes a compound represented by the following formula 1 as a first additive. The compound of the following formula 1 is an oxazolidinone compound, and the film is easily formed by breaking the ring structure on the positive and negative electrode surfaces. Specifically, since the carbon with lower electronegativity than nitrogen and oxygen in the oxazolidinone ring also has a lower electron density than nitrogen and oxygen in the oxazolidinone ring, the carbon is easily reduced on the negative electrode so that a film can be formed. On the contrary, due to the increase in the oxidation number of the transition metal of the positive active material on the positive electrode during charging, the oxygen of C=O in the oxazolidinone ring strongly interacts with the positive electrode, the ring structure may break, and a film may be easily formed. Since the oxazolidinone ring structure breaks into a free radical form to cause an additional cross-linking reaction, a strong and stable film can be formed. In addition, since the nitrogen and oxygen in the oxazolidinone ring structure have unshared electron pairs, when lithium ions are lithiated / delithiated to the positive / negative electrode, a film with high lithium mobility is formed. Therefore, the first additive of the present invention can suppress the deterioration of the passivation ability of SEI at high temperature, thereby preventing the deterioration of the negative electrode and improving the performance of the lithium secondary battery.
[0038] [Formula 1]
[0039]
[0040] In Formula 1, R1 can be selected from any one of the group consisting of an alkyl group having 1 to 5 carbon atoms which is unsubstituted or substituted with fluorine, an alkenyl group having 2 to 5 carbon atoms which is unsubstituted or substituted with fluorine, an alkynyl group having 2 to 5 carbon atoms which is unsubstituted or substituted with fluorine, SO2R' and COR'. Preferably, R1 is preferably substituted with fluorine. In this case, an organic-inorganic composite film can be formed to form a strong and durable film. The film containing an organic component has excellent lithium transfer characteristics, but is prone to side reactions in the acidic atmosphere of the electrolyte, and the inorganic film suppresses side reactions in the acidic atmosphere, but has poor lithium transfer characteristics. Therefore, when an organic-inorganic composite film is formed, the overall characteristics of the lithium secondary battery are maximized.
[0041] R' may be any one selected from the group consisting of an unsubstituted or substituted fluorine alkyl group having 1 to 5 carbon atoms, an unsubstituted or substituted fluorine alkenyl group having 2 to 5 carbon atoms, and an unsubstituted or substituted fluorine alkynyl group having 2 to 5 carbon atoms.
[0042] In Formula 1, R2 and R3 may each independently be any one selected from the group consisting of H, an alkyl group having 1 to 5 carbon atoms, and an alkoxy group having 1 to 5 carbon atoms, and preferably, R2 and R3 may both be H.
[0043] Specifically, the compound of Formula 1 above may be any one of the compounds represented by the following Formulas 1-1 to 1-6.
[0044] [Formula 1-1]
[0045]
[0046] [Formula 1-2]
[0047]
[0048] [Formula 1-3]
[0049]
[0050] [Formula 1-4]
[0051]
[0052] [Formula 1-5]
[0053]
[0054] [Formula 1-6]
[0055]
[0056] The non-aqueous electrolyte of the present invention comprises a compound represented by the following chemical formula 2 or 3 as a second additive. The compound of formula 2 or 3 may include a propargyl group to be easily reduced on the surface of the negative electrode, and can easily form a film on the surface of the negative electrode. Compared with the SEI film formed by the reduction decomposition of a commonly used electrolyte, the film has higher stability and lower electronic conductivity, thereby having the advantage of suppressing additional decomposition reactions of the electrolyte, and the film is not easily damaged by the volume change of the negative electrode. That is, the interfacial stability between the negative electrode and the electrolyte can be ensured by using a compound of formula 2 or 3 as an additive to the electrolyte.
[0057] Since the compound of formula 2 includes a propargyl group (known to have metal ion adsorption properties) and an oxygen atom having a triple bond, the propargyl group separated by the cracking of the nitrogen (N) atom and the carbon (C) atom of the imidazole group can adsorb metal foreign substances such as Fe, Co, Mn and Ni dissolved from the positive electrode during charging at high voltage, thereby effectively suppressing the negative electrode degradation phenomenon that occurs when foreign substances are deposited on the negative electrode surface. In addition, since in the compound represented by formula 2, the lone pair of electrons of the nitrogen (N) atom of the imidazole group can react with an alkyl carbonate (which is a decomposition product of ethylene carbonate (EC) used as an organic solvent) to be reduced on the negative electrode surface, a stable ion conductive film can be formed on the negative electrode surface. Therefore, not only can the additional electrolyte decomposition reaction during charging and discharging be suppressed, but also the retention and release of lithium ions from the negative electrode can become stable during overcharging and high temperature storage, thereby improving the cycle life characteristics and high temperature storage performance of the secondary battery.
[0058] [Formula 2]
[0059]
[0060] In Formula 2, R may be an unsubstituted or substituted fluorine-substituted alkylene group having 1 to 3 carbon atoms, and R4 to R6 may each independently be any one selected from the group consisting of H, an alkyl group having 1 to 3 carbon atoms, and a nitrile group.
[0061] Specifically, the compound of Formula 2 of the present invention may be a compound of the following Formula 2-1.
[0062] [Formula 2-1]
[0063]
[0064] The compound of formula 3 contains an ester functional group and an unsaturated hydrocarbon group in its molecular structure, and decomposes earlier than any other component of the electrolyte during the initial charging process of the secondary battery to form a film having a compound based on a carbon-oxygen single bond (CO) or a carbon-oxygen double bond (C=O) as a main component on the surface of the negative electrode. In addition, the compound of formula 3 may include a propargyl group to easily reduce on the surface of the negative electrode and easily form a film on the surface of the negative electrode. The advantage of the film is that it has a higher stability than the SEI film formed by the reductive decomposition of a commonly used electrolyte, suppresses the additional decomposition reaction of the electrolyte caused by low electronic conductivity, and is not easily damaged even if the volume of the negative electrode changes.
[0065] [Formula 3]
[0066]
[0067] In Formula 3, R7 may be an alkylene group having 1 to 8 carbon atoms which is unsubstituted or substituted with fluorine, and is preferably an alkylene group having 1 to 5 carbon atoms.
[0068] In Formula 3, R8 may be any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
[0069] The compound of Formula 3 may be a compound of the following Formula 3-1.
[0070] [Formula 3-1]
[0071]
[0072] In the above formula 3-1, n may be a natural number of 1 to 8, preferably a natural number of 1 to 5, and most preferably a natural number of 1 to 3.
[0073] In the above formula 3-1, R8 may be H or an alkyl group having 1 to 10 carbon atoms, preferably H or a methyl group.
[0074] Specifically, the compound of Formula 3 of the present invention may be a compound of the following Formula 3-2.
[0075] [Formula 3-2]
[0076]
[0077] When using the non-aqueous electrolyte of the present invention comprising the first additive and the second additive, the film-forming reaction of the second additive is accelerated by the free radicals generated when the ring structure of the first additive is broken. Due to the structure caused by oxazolidinone, imidazole, cyclic carbonate structure or the structure caused by this between the aliphatic alkyl film, the film formed by the interaction of the first additive and the second additive can have excellent lithium ion transfer characteristics to improve the charge and discharge characteristics and output characteristics of the lithium secondary battery. The film formed by the interaction of the first additive and the second additive can have excellent oxidation resistance, thereby suppressing the side reactions occurring on the film of the positive and negative electrodes even in the acidic atmosphere of the electrolyte. In addition, the film formed by the interaction of the first additive and the second additive has excellent durability, even resisting the volume expansion of the negative electrode occurring during charging and discharging. Therefore, the non-aqueous electrolyte of the present invention can form an electrode-electrolyte interface that is stable and durable at high temperatures, and can suppress unnecessary electrolyte decomposition side reactions, thereby realizing a lithium secondary battery with improved overall performance.
[0078] Based on 100 parts by weight of the non-aqueous electrolyte, the content of the first additive in the non-aqueous electrolyte of the present invention may be 0.01 parts by weight to 10 parts by weight, or 0.01 parts by weight to 5 parts by weight, preferably 0.05 parts by weight to 3.0 parts by weight, and more preferably 0.10 parts by weight to 2.0 parts by weight. When the content of the first additive satisfies this range, it has a sufficient film-forming effect on the negative electrode, and thus has excellent high temperature life characteristics and storage characteristics.
[0079] Based on 100 parts by weight of the non-aqueous electrolyte, the content of the second additive in the non-aqueous electrolyte of the present invention may be 0.01 parts by weight to 5 parts by weight, preferably 0.05 parts by weight to 3.0 parts by weight, and more preferably 0.10 parts by weight to 2.5 parts by weight. When the content of the second additive satisfies this range, it has a sufficient film-forming effect on the negative electrode, and thus has excellent high temperature life characteristics and storage characteristics.
[0080] The content ratio of the first additive and the second additive in the non-aqueous electrolyte of the present invention may be 1:0.001 to 1:500 parts by weight, or 1:0.002 to 1:500 parts by weight, preferably 1:0.01 to 1:300 parts by weight, and most preferably 1:0.02 to 1:250 parts by weight. When this range is met, the elasticity of the SEI film may be within an appropriate range, thereby firmly maintaining the SEI film during charge and discharge or at high temperatures.
[0081] The non-aqueous electrolyte of the present invention may include a lithium salt. The lithium salt is used as an electrolyte salt in a lithium secondary battery and a medium for transferring ions. Generally, the lithium salt may include Li +as a cation, and may include as an anion at least any one selected from the group consisting of: F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .
[0082] Specifically, the lithium salt may include a lithium salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiPF6, LiSO3CF3, LiCO2CH3, LiCO2CF3, LiAsF6, LiSbF6, LiSO3CH3, LiN(SO2F)2(lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF2CF3)2(lithium bis(perfluoroethanesulfonyl)imide, LiBETI) and LiN(SO2CF3)2(lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), or a mixture of two or more thereof. In addition to the above, lithium salts commonly used in electrolytes for lithium secondary batteries can also be used without restriction.
[0083] The lithium salt may be appropriately changed within a generally available range, but may be included in an electrolyte at a concentration of 0.5 M to 5.0 M, preferably 1.0 M to 3.0 M, and more preferably 1.2 M to 2.0 M, so as to obtain an optimized film formation effect for preventing corrosion on the electrode surface. When the concentration of the lithium salt satisfies this range, a sufficient effect of improving cycle characteristics may be achieved when the lithium secondary battery is stored at high temperatures, and electrolyte impregnation may be improved due to the appropriate viscosity of the non-aqueous electrolyte.
[0084] The non-aqueous electrolyte of the present invention may include an organic solvent. The organic solvent may include at least one organic solvent selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, and a cyclic ester organic solvent.
[0085] When using cyclic carbonate solvent, additive of the present invention is especially effective.When conventional electrolyte additive is used together with cyclic carbonate solvent, the limitation of existence is, due to the change of negative electrode volume occurring during the cycle period, it is difficult to maintain the SEI film formed by the decomposition of cyclic carbonate solvent, so solvent is constantly decomposed.Therefore, the limitation of existence is, the ionic conductivity of electrolyte reduces, so the cycle characteristic deteriorates.But, when using cyclic carbonate solvent and additive of the present invention in combination, it is possible to form a stable SEI film, therefore there is the effect of keeping excellent cycle characteristic.
[0086] The cyclic carbonate organic solvent is an organic solvent with high viscosity and can well dissociate the lithium salt in the electrolyte due to its high dielectric constant, and specific examples of the cyclic carbonate organic solvent may include at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, and fluoroethylene carbonate (FEC) may be included therein.
[0087] In addition, the linear carbonate organic solvent is an organic solvent having low viscosity and a low dielectric constant, and representative examples may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methylpropyl carbonate and ethylpropyl carbonate, and diethyl carbonate (DEC) may be included therein.
[0088] Furthermore, in order to prepare an electrolyte having high ionic conductivity, in addition to at least one carbonate organic solvent selected from the group consisting of cyclic carbonate organic solvents and linear carbonate organic solvents, at least one ester organic solvent selected from the group consisting of linear ester organic solvents and cyclic ester organic solvents may be included.
[0089] Specific examples of the linear ester organic solvent may be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0090] In addition, the cyclic ester organic solvent may be at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0091] Meanwhile, if necessary, the organic solvent may be used by adding any organic solvent commonly used in non-aqueous electrolytes without limitation. For example, at least one of an ether organic solvent, a glyme organic solvent, and a nitrile organic solvent may be additionally included.
[0092] As the ether solvent, any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more thereof may be used, but the ether solvent is not limited thereto.
[0093] The glyme-based solvent is a solvent having a higher dielectric constant and a lower surface tension than a linear carbonate-based organic solvent and having a lower reactivity with a metal, and may include at least one selected from the group consisting of dimethoxyethane (glyme, DME), diethoxyethane, diglyme, triglyme and tetraglyme (TEGDME), but the glyme-based solvent is not limited thereto.
[0094] The nitrile solvent may be at least one of the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzene acetonitrile and 4-fluorobenzene acetonitrile, but the nitrile solvent is not limited thereto.
[0095] In addition, as needed, the non-aqueous electrolyte of the present invention may further contain known electrolyte additives to prevent negative electrode collapse caused by decomposition of the non-aqueous electrolyte, or to further improve low-temperature and high-efficiency discharge characteristics, high-temperature stability, prevent overcharging, and inhibit the expansion of the battery at high temperatures, etc.
[0096] Representative examples of such additional electrolyte additives may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate compounds, halogenated carbonate compounds, sultone compounds, sulfate ester / salt compounds, phosphate ester / salt compounds, borate ester / salt compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds and lithium salt compounds.
[0097] The cyclic carbonate compound may be vinylene carbonate (VC) or vinyl ethylene carbonate.
[0098] The halogenated carbonate compound may be fluoroethylene carbonate (FEC).
[0099] The sultone compound may be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethylene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0100] The sulfate compound may be ethylene sulfate (Esa), trimethylene sulfate (TMS) or tripropylene methyl sulfate (MTMS).
[0101] The phosphate compound may be at least one selected from the group consisting of lithium difluorobis(oxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate and tris(2,2,2-trifluoroethyl)phosphite.
[0102] The borate ester / salt compound may be tetraphenylborate, lithium difluoro(oxalato)borate (LiODFB) and lithium bis(oxalato)borate (LiB(C2O4)2, LiBOB).
[0103] The nitrile compound may be at least one selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzoyl cyanide and 4-fluorobenzoyl cyanide.
[0104] The benzene compound may be fluorobenzene, the amine compound may be triethanolamine or ethylenediamine, and the silane compound may be tetravinylsilane.
[0105] The lithium salt compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, and may be lithium difluorophosphate (LiDFP), LiPO2F2, LiBF4, or the like.
[0106] Among these additional electrolyte additives, when a combination of vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (Esa) and lithium difluorophosphate (LiDFP) is additionally included, a more stable SEI film can be formed on the negative electrode surface during the initial activation process of the secondary battery, and the high temperature stability of the secondary battery can be improved by suppressing gas generation that may be caused by decomposition of the electrolyte at high temperature.
[0107] Meanwhile, at least two additional electrolyte additives may be mixed and used, and the amount of the additional electrolyte additive may be 0.050 wt % to 20 wt %, specifically 0.10 wt % to 15 wt %, preferably 0.30 wt % to 10 wt %, based on the total weight of the non-aqueous electrolyte. When the content of the additional electrolyte additive satisfies this range, the effects of improving ion conductivity and cycle characteristics become more excellent.
[0108] Lithium secondary battery
[0109] The present invention provides a lithium secondary battery comprising the non-aqueous electrolyte.
[0110] Specifically, the lithium secondary battery includes: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and the above-mentioned nonaqueous electrolyte.
[0111] In this case, the lithium secondary battery of the present invention can be manufactured according to a method generally known in the art. For example, the lithium secondary battery of the present invention can be manufactured by the following process: after stacking the positive electrode, the negative electrode and the separator between the positive electrode and the negative electrode in sequence to form an electrode assembly, the electrode assembly is inserted into the interior of the battery housing and the non-aqueous electrolyte of the present invention is injected.
[0112] (1) Positive electrode
[0113] The positive electrode may be manufactured by coating a positive electrode mixture slurry including a positive electrode active material, a binder, a conductive material, a solvent, and the like on a positive electrode collector.
[0114] The positive electrode collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used as the positive electrode collector.
[0115] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium, and specifically includes lithium metal oxides containing lithium and at least one metal (such as cobalt, manganese, nickel, or aluminum). More specifically, the lithium metal oxide can be lithium manganese oxide (such as LiMnO2, LiMn2O4, etc.), lithium cobalt oxide (such as LiCoO2, etc.), lithium nickel oxide (such as LiNiO2, etc.), lithium nickel manganese oxide (such as, LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < z < 2), etc.), lithium nickel cobalt oxide (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium manganese cobalt oxide (such as, LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < z1 < 2), etc.), lithium nickel manganese cobalt oxide (such as, Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, and p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, and p1 + q1 + r1 = 2), etc.), or lithium nickel cobalt transition metal (M) oxide (such as, Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are the atomic fractions of the respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc.), and may include any one or at least two of these compounds.
[0116] Among these materials, in terms of improving the capacity characteristics and stability of the battery, the lithium metal oxide can be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (such as Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (such as Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), etc., and any one or a mixture of at least two of them can be used.
[0117] In order to maximize the capacity characteristics of the battery, a positive electrode active material with a nickel content of at least 80 atm% can be used. For example, the lithium transition metal oxide may include a compound represented by the following formula 4.
[0118] [Formula 4]
[0119] Li x Ni a Co b M 1 c M 2 d O2
[0120] In the above formula 4, M 1 can be at least one selected from Mn and Al, preferably Mn, or a combination of Mn and Al.
[0121] M 2 can be at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb.
[0122] x is the atomic fraction of lithium in the lithium transition metal oxide, and can be 0.90 ≤ x ≤ 1.1, preferably 0.95 ≤ x ≤ 1.08, and more preferably 1.0 ≤ x ≤ 1.08.
[0123] a is the atomic fraction of nickel in the metal elements other than lithium in the lithium transition metal oxide, and can be 0.80 ≤ a < 1.0, preferably 0.80 ≤ a ≤ 0.95, and more preferably 0.85 ≤ a ≤ 0.90.
[0124] b is the atomic fraction of cobalt in the metal elements other than lithium in the lithium transition metal oxide, and can be 0 < b < 0.2, preferably 0 < b ≤ 0.15, and more preferably 0.01 ≤ b ≤ 0.10.
[0125] c is M in the metal elements other than lithium in the lithium transition metal oxide 1The atomic fraction of c, and it can be 0 < c < 0.2, preferably 0 < c ≤ 0.15, and more preferably 0.01 ≤ c ≤ 0.10.
[0126] d is the atomic fraction of M among the metal elements other than lithium in the lithium transition metal oxide 2 and it can be 0 ≤ d ≤ 0.1, preferably 0 ≤ d ≤ 0.05.
[0127] Based on the total weight of the solids other than the solvent in the positive electrode mixture slurry, the content of the positive electrode active material can be 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, and more preferably 80% by weight to 98% by weight.
[0128] The binder is a component that helps the binding of the active material and the conductive material and the binding with the current collector.
[0129] The binder can be, for example, polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene - propylene - diene monomer, sulfonated ethylene - propylene - diene monomer, styrene - butadiene rubber, fluororubber, and various copolymers, etc.
[0130] Generally, based on the total weight of the solids other than the solvent in the positive electrode material mixture slurry, the content of the binder can be 1% by weight to 20% by weight, preferably 1% by weight to 15% by weight, and more preferably 1% by weight to 10% by weight.
[0131] The conductive material is a component used to further improve the conductivity of the positive electrode active material, and it can be added in an amount of 1% by weight to 20% by weight based on the total weight of the solids of the positive electrode mixture slurry. There is no particular limitation on the conductive material as long as it has conductivity without causing chemical changes in the battery. As the conductive material, the following can be used: carbon powders such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal cracking carbon black; graphite powders such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers or metal fibers; carbon fluoride powders; conductive powders such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.
[0132] Generally, based on the total weight of the solids other than the solvent in the positive electrode material mixture slurry, the content of the conductive agent can be 1% by weight to 20% by weight, preferably 1% by weight to 15% by weight, and more preferably 1% by weight to 10% by weight.
[0133] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a preferred viscosity is obtained when a positive electrode active material and an optional binder and a conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid matter containing the positive electrode active material and the optional binder and conductive agent is 50 wt % to 95 wt %, preferably 70 wt % to 95 wt %, and more preferably 70 wt % to 90 wt %.
[0134] (2) Negative electrode
[0135] The negative electrode may be manufactured, for example, by coating a negative electrode mixture slurry including a negative electrode active material, a binder, a conductive material, a solvent, etc. on a negative electrode collector, or a graphite electrode composed of carbon (C) or metal itself may be used as the negative electrode.
[0136] For example, when the negative electrode is manufactured by applying the negative electrode mixture slurry to the negative electrode collector, the negative electrode collector generally has a thickness of 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel treated with carbon, nickel, titanium, silver, etc. on the surface, aluminum-cadmium alloy, etc. can be used as the negative electrode collector. In addition, like the positive electrode collector, the binding force of the negative electrode active material can be enhanced by forming fine irregularities on the surface of the negative electrode collector, and the negative electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0137] In addition, the negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of lithium and the metal, a metal composite oxide, a material doped and dedoped with lithium, and a transition metal oxide.
[0138] As long as it is a carbon-based negative electrode active material commonly used in lithium ion secondary batteries, it is possible to use a carbon material capable of reversibly embedding / de-embedding lithium ions without particular limitation, and as a representative example, crystalline carbon or amorphous carbon can be used alone or together. The example of crystalline carbon can be graphite, such as irregular, planar, thin, spherical or fibrous natural graphite or artificial graphite. The example of amorphous carbon can be soft carbon (low temperature sintered carbon) or hard carbon, mesophase pitch carbide and fired coke.
[0139] As the metal or the alloy of lithium and the metal, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn, or an alloy of lithium and the metal can be used.
[0140] The metal composite oxide may be a material selected from the group consisting of: PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, and Ge; Me': Al, B, P, Si, elements of Groups 1, 2, and 3 of the periodic table, or a halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8).
[0141] The material that can be doped and undoped with lithium may include Si, SiO x (0 < x ≤ 2), Si - Y alloy (where Y is an element selected from the group consisting of: alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, and Sn - Y (where Y is an element selected from the group consisting of: alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), and SiO2 and at least one of them can be used in combination. The element Y may be selected from the group consisting of: Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof).
[0142] The transition metal oxide may include lithium - containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.
[0143] When Si or SiO x (0 < x ≤ 2) is used as the negative electrode active material, the additive of the present invention is very effective. Specifically, when using an Si - based negative electrode active material, if a stable SEI layer is not formed on the negative electrode surface during the initial activation process, the extreme volume expansion / contraction during cycling will promote the deterioration of the life characteristics. However, the additive of the present invention can form an elastic and stable SEI layer, thereby making the life characteristics and storage characteristics of the secondary battery using the Si - based negative electrode active material excellent.
[0144] The content of the negative electrode active material may be 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, based on the total solid weight of the negative electrode mixture slurry.
[0145] For example, the binder can be polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and various copolymers thereof, etc. Specifically, styrene-butadiene rubber (SBR)-carboxymethyl cellulose (CMC) can be used for high thickening performance.
[0146] Generally, the binder may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.
[0147] The conductive material is a component for further improving the conductivity of the negative electrode active material, and can be added in an amount of 1 wt % to 20 wt % based on the total solid weight of the negative electrode mixture slurry. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, the following conductive materials can be used: carbon powder, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a highly developed crystal structure; conductive fibers, such as carbon fibers and metal fibers; fluorinated carbon powder; conductive powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc.
[0148] The content of the conductive material may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.
[0149] The solvent may include an organic solvent such as water or N-methyl-2-pyrrolidone (NMP), and may be used in an amount that provides a preferred viscosity when including the negative electrode active material and optional binder and conductive material. For example, the content of the solvent may be such that the concentration of the solid including the negative electrode active material and optional binder and conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %.
[0150] When the metal itself is used, the negative electrode can be manufactured by physically bonding, rolling or depositing the metal on the metal film itself or the negative electrode current collector. The deposition method can be a method of electrodeposition or chemical deposition of the metal.
[0151] For example, the metal bonded / rolled / deposited on the metal film itself or the negative electrode current collector may include one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two metals thereof.
[0152] (3) Diaphragm
[0153] In addition, as a separator, a porous polymer film conventionally used as a separator, for example, a porous polymer film made of a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-methacrylate copolymer) can be used alone, or they can be stacked together, or a typical porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber, but the separator is not limited thereto. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure can be selectively used.
[0154] Specifically, a safety reinforced separator (SRS) on which a coating layer including a ceramic component or a polymer material is formed in order to ensure heat resistance or mechanical strength may be used as the separator included in the electrode assembly of the present invention.
[0155] Specifically, the separator contained in the electrode assembly of the present invention may include a porous separator substrate, and a porous coating completely coated on one surface or both surfaces of the separator substrate, and the coating may include a mixture of inorganic particles selected from metal oxides, metalloid oxides, metal fluorides, metal hydroxides and combinations thereof, and a binder polymer for connecting and fixing the inorganic particles to each other.
[0156] The coating may include at least one selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, and MgF as inorganic particles. In this case, the inorganic particles can improve the thermal stability of the separator. That is, the inorganic particles can prevent the separator from shrinking at high temperatures. In addition, the binder polymer can fix the inorganic particles to improve the mechanical stability of the separator.
[0157] The external form of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical form using a can, an angular form, a pouch form, a coin form, or the like.
[0158] Hereinafter, the present invention will be described in more detail by specific examples. However, the following examples are only for helping to understand embodiments of the present invention, and do not limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications within the scope and technical spirit of this specification are possible, and these changes and modifications naturally fall within the scope of the attached patent claims.
[0159] Example
[0160] Example 1
[0161] (Preparation of non-aqueous electrolyte)
[0162] A non-aqueous solvent was prepared by dissolving LiPF6 in an organic solvent (volume ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 20:70:10) to 1.2 M, and a non-aqueous electrolyte was prepared by placing 0.01 g of the compound of the following formula 1-1 and 0.01 g of the compound of the following formula 2-1 into 99.98 g of the non-aqueous solvent.
[0163] [Formula 1-1]
[0164]
[0165] [Formula 2-1]
[0166]
[0167] (Manufacturing of lithium secondary batteries)
[0168] By 0.85 Co 0.05 Mn 0.08 Al 0.02 O2), conductive material (carbon nanotubes) and binder (polyvinylidene fluoride) were added to solvent N-methyl-2-pyrrolidone (NMP) at a weight ratio of 97.74:0.7:1.56 to prepare a positive electrode slurry (75.5 wt% solid). The positive electrode was manufactured by coating, drying and rolling the positive electrode slurry on one surface of a positive electrode current collector (aluminum film) with a thickness of 15 μm.
[0169] The negative electrode slurry was prepared by adding the negative electrode active material (Si), the conductive material (carbon black) and the binder (styrene-butadiene rubber (SBR)-carboxymethyl cellulose (CMC)) to the solvent N-methyl-2-pyrrolidone (NMP) at a weight ratio of 70:20.3:9.7. The negative electrode was manufactured by coating, drying and rolling the negative electrode slurry on one surface of the negative electrode current collector (copper film) with a thickness of 15 μm.
[0170] A secondary battery was manufactured by placing a polyolefin-based porous separator coated with inorganic particles of Al2O3 between the manufactured positive and negative electrodes in a dry room and then pouring the manufactured nonaqueous electrolyte.
[0171] Example 2
[0172] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 3-2 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0173] [Formula 3-2]
[0174]
[0175] Example 3
[0176] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 1-1 and 5 g of the compound of Formula 2-1 into 94.99 g of the nonaqueous solvent prepared in Example 1.
[0177] Example 4
[0178] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 1-1 and 5 g of the compound of Formula 3-2 into 94.99 g of the nonaqueous solvent prepared in Example 1.
[0179] Example 5
[0180] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 10 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 2-1 into 89.99 g of the nonaqueous solvent prepared in Example 1.
[0181] Example 6
[0182] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 10 g of the compound of Formula 1-1 and 0.01 g of the compound of Formula 3-2 into 89.99 g of the nonaqueous solvent prepared in Example 1.
[0183] Example 7
[0184] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 10 g of the compound of Formula 1-1 and 5 g of the compound of Formula 2-1 into 85 g of the nonaqueous solvent prepared in Example 1.
[0185] Example 8
[0186] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 10 g of the compound of Formula 1-1 and 5 g of the compound of Formula 3-2 into 85 g of the nonaqueous solvent prepared in Example 1.
[0187] Example 9
[0188] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of the following Formula 1-2 and 0.01 g of the compound of Formula 2-1 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0189] [Formula 1-2]
[0190]
[0191] Example 10
[0192] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of the following Formula 1-3 and 0.01 g of the compound of Formula 2-1 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0193] [Formula 1-3]
[0194]
[0195] Embodiment 11
[0196] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of the following Formula 1-4 and 0.01 g of the compound of Formula 2-1 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0197] [Formula 1-4]
[0198]
[0199] Example 12
[0200] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of the following Formula 1-5 and 0.01 g of the compound of Formula 2-1 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0201] [Formula 1-5]
[0202]
[0203] Embodiment 13
[0204] A secondary battery was manufactured by the same method as Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of the following Formula 1-6 and 0.01 g of the compound of Formula 2-1 into 99.98 g of the nonaqueous solvent prepared in Example 1.
[0205] [Formula 1-6]
[0206]
[0207] Comparative Example 1
[0208] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 1-1 into 99.99 g of the nonaqueous solvent prepared in Example 1.
[0209] Comparative Example 2
[0210] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 10 g of the compound of Formula 1-1 into 90 g of the nonaqueous solvent prepared in Example 1.
[0211] Comparative Example 3
[0212] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 2-1 into 99.99 g of the nonaqueous solvent prepared in Example 1.
[0213] Comparative Example 4
[0214] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 5 g of the compound of Formula 2-1 into 95 g of the nonaqueous solvent prepared in Example 1.
[0215] Comparative Example 5
[0216] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 0.01 g of the compound of Formula 3-2 into 99.99 g of the nonaqueous solvent prepared in Example 1.
[0217] Comparative Example 6
[0218] A secondary battery was manufactured by the same method as in Example 1, except that a nonaqueous electrolyte was prepared by introducing 5 g of the compound of Formula 3-2 into 95 g of the nonaqueous solvent prepared in Example 1.
[0219] Experimental Example 1-Evaluation of High Temperature Cycle Characteristics
[0220] The cycle characteristics of each of the secondary batteries manufactured in Examples 1 to 13 and Comparative Examples 1 to 6 were evaluated.
[0221] Specifically, each battery manufactured in Examples 1 to 13 and Comparative Examples 1 to 6 was subjected to 200 charge and discharge cycles, wherein each cycle consisted of charging to 4.2V at a rate of 0.33C under constant current / constant voltage conditions at 45°C, followed by discharging to 3.0V at a constant current of 0.33C, and then measuring the capacity retention rate of the battery after 200 cycles relative to the initial capacity of the battery after 1 cycle. In addition, the resistance increase rate of the battery after 200 cycles relative to the initial resistance of the battery after 1 cycle was measured. The results are shown in Table 1 below.
[0222] [Table 1]
[0223] Capacity retention rate (%) Resistance increase rate (%) Example 1 90 6 Example 2 92 8 Example 3 91 8 Example 4 90 6 Example 5 91 8 Example 6 90 7 Example 7 91 7 Example 8 90 6 Example 9 90 6 Example 10 90 5 Embodiment 11 91 7 Example 12 90 5 Embodiment 13 91 7 Comparative Example 1 84 19 Comparative Example 2 82 20 Comparative Example 3 81 17 Comparative Example 4 84 20 Comparative Example 5 84 19 Comparative Example 6 82 19
[0224] Experimental Example 2-Evaluation of High Temperature Storage Characteristics
[0225] The high-temperature storage characteristics of each of the secondary batteries manufactured in Examples 1 to 13 and Comparative Examples 1 to 6 were evaluated.
[0226] Specifically, after being fully charged to 4.2 V, each of the secondary batteries of Examples 1 to 13 and Comparative Examples 1 to 6 was stored at 60° C. for 8 weeks.
[0227] Before storage, the capacity of the fully charged secondary battery was measured and set as the initial capacity of the secondary battery.
[0228] After 8 weeks, the capacity of the secondary battery after storage was measured to calculate the capacity reduced by the storage period of 8 weeks. By calculating the percentage of the reduced capacity to the initial capacity of the secondary battery, the capacity retention rate after 8 weeks was obtained. In addition, by calculating the percentage of the increased resistance to the initial resistance of the secondary battery, the resistance increase rate after 8 weeks was obtained. The results are shown in Table 2 below.
[0229] [Table 2]
[0230] Capacity retention rate (%) Resistance increase rate (%) Example 1 95 7 Example 2 96 8 Example 3 95 7 Example 4 95 7 Example 5 96 7 Example 6 94 6 Example 7 95 8 Example 8 94 7 Example 9 95 7 Example 10 96 9 Embodiment 11 94 6 Example 12 96 8 Embodiment 13 95 7 Comparative Example 1 85 16 Comparative Example 2 87 21 Comparative Example 3 86 20 Comparative Example 4 85 17 Comparative Example 5 86 20 Comparative Example 6 83 17
[0231] Experimental Example 3-Evaluation of Thermal Stability
[0232] The thermal stability of each of the secondary batteries manufactured in Examples 1 to 13 and Comparative Examples 1 to 6 was evaluated.
[0233] Specifically, after the formation process, the lithium secondary batteries manufactured in the embodiments and comparative examples were charged to 4.2V (0.05C cutoff) under constant current / constant voltage conditions at a rate of 0.33C at 25°C to fully charge to 100% SOC. A hot box evaluation experiment was performed to confirm whether ignition occurred when the fully charged battery was heated to 140°C at a heating rate of 5°C / min and left for 1 hour. The situation where no ignition occurred was evaluated as "passed", and the situation where ignition occurred was evaluated as "failed", and the results are shown in Table 3 below.
[0234] [Table 3]
[0235] Hot Box Test Results Example 1 pass Example 2 pass Example 3 pass Example 4 pass Example 5 pass Example 6 pass Example 7 pass Example 8 pass Example 9 pass Example 10 pass Embodiment 11 pass Example 12 pass Embodiment 13 pass Comparative Example 1 Failed Comparative Example 2 pass Comparative Example 3 Failed Comparative Example 4 Failed Comparative Example 5 Failed Comparative Example 6 Failed
Claims
1. A non-aqueous electrolyte comprising: Lithium salts; Organic solvents; A compound of the following Formula 1 as a first additive; and As the second additive, a compound of the following formula 2 or formula 3, [Formula 1] in, In the above formula 1, R1 is any one selected from the group consisting of an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine, an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine, SO2R' and COR', R' is any one selected from the group consisting of an alkyl group having 1 to 5 carbon atoms which may be substituted with fluorine, an alkenyl group having 2 to 5 carbon atoms which may be substituted with fluorine, and an alkynyl group having 2 to 5 carbon atoms which may be substituted with fluorine, and R2 and R3 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 5 carbon atoms, and an alkoxy group having 1 to 5 carbon atoms, [Formula 2] Wherein, in the above formula 2, R is an alkylene group having 1 to 3 carbon atoms which can be substituted with fluorine, R4 to R6 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 3 carbon atoms, and a nitrile group, [Formula 3] Wherein, in the above formula 3, R7 is an alkylene group having 1 to 8 carbon atoms which can be substituted with fluorine, R8 is any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and a cycloalkyl group having 3 to 8 carbon atoms.
2. The non-aqueous electrolyte according to claim 1, wherein The compound of the above formula 1 is any one selected from the following formulas 1-1 to 1-6: [Formula 1-1] [Formula 1-2] [Formula 1-3] [Formula 1-4] [Formula 1-5] [Formula 1-6] 3. The non-aqueous electrolyte according to claim 1, wherein The compound of the above formula 2 is the compound of the following formula 2-1: [Formula 2-1] 4. The non-aqueous electrolyte according to claim 1, wherein The compound of the above formula 3 is a compound of the following formula 3-1, [Formula 3-1] Among them, in the above formula 3-1, n is a natural number from 1 to 8, and R8 is H or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms.
5. The non-aqueous electrolyte according to claim 1, wherein The compound of the above formula 3 is the compound of the following formula 3-2: [Formula 3-2] 6. The non-aqueous electrolyte according to claim 1, wherein The nonaqueous electrolyte includes the first additive in an amount of 0.01 parts by weight to 10 parts by weight based on 100 parts by weight of the nonaqueous electrolyte.
7. The nonaqueous electrolyte according to claim 1, wherein The nonaqueous electrolyte includes the second additive in an amount of 0.01 parts by weight to 5 parts by weight based on 100 parts by weight of the nonaqueous electrolyte.
8. The nonaqueous electrolyte according to claim 1, wherein The nonaqueous electrolyte includes the first additive and the second additive in a weight ratio of 1:0.001 to 1:
500.
9. The nonaqueous electrolyte according to claim 1, wherein The lithium salt is selected from LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiSO3CF3, LiCO2CH3, LiCO2CF3, LiAsF6, LiSbF6, LiSO3CH3, LiN(SO2F)2, LiN(SO2CF2CF3)2 and at least one of the group consisting of LiN(SO2CF3)2.
10. The non-aqueous electrolyte according to claim 1, wherein The non-aqueous electrolyte includes a lithium salt at a concentration of 0.5M to 5.0M.
11. The non-aqueous electrolyte according to claim 1, wherein The organic solvent includes at least one organic solvent selected from the group consisting of a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, a linear ester-based organic solvent, and a cyclic ester-based organic solvent.
12. A lithium secondary battery comprising: a positive electrode, the positive electrode comprising a positive electrode active material layer; A negative electrode, the negative electrode comprising a negative electrode active material layer; and The non-aqueous electrolyte according to any one of claims 1 to 11.
13. The lithium secondary battery according to claim 12, wherein: The positive electrode active material layer includes a lithium nickel-based oxide represented by the following Formula 4 as a positive electrode active material: [Formula 4] Li x Ni a Co b M 1 c M 2 d O2 Among them, in the above formula 4, M 1 is Mn, Al or a combination thereof, M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, and 0.90≤x≤1.1,0.80≤a<1.0,0<b<0.2,0<c<0.2,0≤d≤0.1。 14. The lithium secondary battery according to claim 12, wherein: The negative electrode active material layer comprises SiO x As negative electrode active material, where 0≤x<2.